Atomistic Modeling of Short Pulse Laser Ablation of Metals: Connections between Melting, Spallation, and Phase Explosion - Zhigilei, Leonid V; Lin, Zhibin; Ivanov, Dmitriy S (Journal of physical chemistry. C, 2009)
The mechanisms of short pulse laser interactions with a metal target are investigated in simulations performed with a model combining the molecular dynamics method with a continuum description of laser excitation, electron−phonon equilibration, and electron heat conduction. Three regimes of material response to laser irradiation are identified in simulations performed with a 1 ps laser pulse, which corresponds to the condition of stress confinement: melting and resolidification of a surface region of the target, photomechanical spallation of a single or multiple layers or droplets, and an explosive disintegration of an overheated surface layer (phase explosion). The processes of laser melting, spallation, and phase explosion are taking place on the same time scale and are closely intertwined with each other. The transition to the spallation regime results in a reduction of the melting zone and a sharp drop in the duration of the melting and resolidification cycle. The transition from spallation to phase explosion is signified by an abrupt change in the composition of the ejected plume (from liquid layers and/or large droplets to a mixture of vapor-phase atoms, small clusters and droplets), and results in a substantial increase in the duration of the melting process. In simulations performed with longer, 50 ps, laser pulses, when the condition for stress confinement is not satisfied, the spallation regime is absent and phase explosion results in smaller values of the ablation yield and larger fractions of the vapor phase in the ejected plume as compared to the results obtained with a 1 ps pulse. The more vigorous material ejection and higher ablation yields, observed in the simulations performed with the shorter laser pulse, are explained by the synergistic contribution of the laser-induced stresses and the explosive release of vapor in phase explosion occurring under the condition of stress confinement.